Board of directors' effectiveness and operational risk disclosure on Indonesian Islamic bank performance: The mediating effect of sharia supervisory board quality - Yulianti, Yulianti; Haribowo, Ismawati (al-Uqud : Journal of Islamic Economics, 2024)
Islamic banks today offer several financial and investment options. Despite being designated as a "newcomer," Islamic banks in Indonesia are growing. Islamic banks in Indonesia require solid governance to boost their performance. This study investigates the effectiveness of the board of directors and the impact of operational risk disclosure on performance, using the Sharia supervisory board as a moderator. This study's population consists of Islamic banks in Indonesia that are listed on the Indonesia Stock Exchange between 2016 and 2020. This study uses the purposive sampling method. The criteria of sample selection is Islamic commercial banks in Indonesia publish yearly financial reports from 2016 to 2020 and have released financial statements using the rupiah currency unit. This study used a moderate regression test with the Minitab programme. This study result indicates that disclosing operational risk has a negative impact on performance. Furthermore, a skilled Sharia supervisory board can improve the disclosure of operational risk to the performance of Islamic banks.